Reconstruction of war damaged buildings - a problem that still stands. The case of the national economy bank in Warsaw restored during the second world war = Naprawa uszkodzeń powstałych w wyniku bombardowania - problem (znowu) aktualny. Przykład budynku banku gospodarstwa krajowego odbudowanego w czasie drugiej wojny światowej - Łotysz, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Polish national historiography remains silent on the reconstruction of damaged towns and cities that was undertaken by the German administration after capturing Poland in September 1939. This paper, on the war-time restoration of the National Economy Bank`s headquarters in Warsaw, is an attempt to at least partially fill the gap. Designed by celebrated architect Rudolf Świerczyński in the late 1920s in accordance with contemporary air raid defence regulations, it was bombed and nevertheless seriously damaged during the September Campaign. Under the German management of the bank, the building was reconstructed and even modernized by commissioned Polish engineers.
Keywords: reconstruction; war damages; reinforced concrete; modernism; remonty; uszkodzenia wojenne; modernizm